Criminal Liability In The Practice Of Premanism With The Modus Operandi Of Mass Organizations In Extortion Crimes According To Article 368 Of The Criminal Code - Titi, Swara; Fahrian, Yudi; Agustian, Sakinah (Fakultas Hukum Dehasen, 2025)
This study examines criminal liability in the practice of vigilantism that exploits community organizations (ormas) as a means or modus operandi for committing extortion as regulated under Article 368 of the Indonesian Criminal Code (KUHP). The research focuses on two main aspects: the form of criminal liability imposed on perpetrators who use the identity of ormas to commit extortion, and the factors that contribute to the prevalence of this phenomenon in society. The objective of this research is to comprehensively analyze the application of criminal liability to offenders from the perspective of national criminal law, as well as to reveal the underlying causes of vigilantism disguised under the cover of ormas. The research employs a normative juridical method with a statute approach, supported by literature review of legislation and legal scholarship. The findings indicate that extortion committed by individuals acting under the name of ormas fulfills the criminal elements stipulated in Article 368 of the KUHP, thereby placing primary criminal liability on individual perpetrators. However, if it can be proven that a legal entity benefits from and is involved in such extortion, then the ormas, as a corporation, may also be held criminally liable through the doctrine of corporate criminal liability. The persistence of this phenomenon is influenced by weak governmental oversight, low legal awareness among the public, and the misuse of organizational legitimacy. Addressing this issue requires a comprehensive strategy, including both repressive and preventive legal approaches, strict supervision of ormas activities, enhancement of public legal awareness, and revitalization of regulations concerning corporate criminal liability in cases of extortion.